Economic policy. - b (Oxford : Oxford University Press, 1985)
Economic Policy is at the forefront of economic policy debate. Since its inception, Economic Policy has published some of the most cited studies anywhere in the world - on financial crises, deregulation, unions, the euro and other pressing international topics.
"Published on behalf of Center for Economic Studies of the University of Munich"--Home page.
Description based on online resource; title from home page (viewed on September 29, 2016).
Keywords: Economic policy -- Periodicals; Economics -- Periodicals